Dinamika dalam Relasi Sosial Tim UNY Esport - Akbar, Rizki; Hendrastomo, Grendi (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2024)
Abstract This research aims to determine the social relations of UNY Esport members outside the scope of the esports team. Esports is a competition where players compete online or offline in certain games, often in games requiring interaction and cooperation as a team either directly or virtually with fellow players. Although these interactions build social relations, there are factors that hinder the maintenance of social relations in both worlds. The theory used in this research is the simulacrum theory by Jean Baudrillard. The method used in this research is a qualitative method with descriptive analysis. The informants in this research were 5 members of the UNY Esport Team with the criteria of being part of the main team of each gaming division, being active and having participated in activities and competing with UNY Esport, and were willing to provide information openly. The data collection techniques used in this research were observation, interviews and documentation studies. The research results show that UNY Esports team members experience difficulties in integrating social relations in the real and virtual worlds. Their online identity is not fully connected to their real identity, even through social media. Nevertheless, they show professionalism in virtual communication, especially in the esports context. The relationship between the virtual and real worlds which tend to be separated makes it difficult for members to build social relationships, this is influenced by the team selection process, lack of opportunities and low levels of interaction in the real world. Keywords: esports, social relations, virtual social relations.